Localizing UNSCR 1325 in Indonesia: Study of Local Women Religious Groups in Peacebuilding and Counter Radicalization - Nuriyeni Kartika Bintarsari; Ayusia Sabhita Kusuma; Nurul Azizah Zayzda (Global Strategis, 2022)
The adoption of UNSCR 1325 in Indonesia is a signifcant stage in recognizing women’s role in the peace process at the national and locallevels. This research is interested in examining how local communities, especially religious groups, perform their agency in peace-building, specifically counter-radicalization. This research questions the perception and strategies of women Quran study groups in Cilacap regency in counterradicalization eﬀorts and later provides an overview of peace-building and counter-radicalization activities by women religious groups in Cilacap. The research shows that these women religious groups’ perceptions on radicalization inﬂuence their understanding as an agency in various counter-radicalization activities and contribute to building the foundation of peace in the community by strengthening society’s resilience through social and religious activities.Adopsi UNSCR 1325 di Indonesia menjadi satu tahapan yang signifkan untuk mengakui peran perempuan dalam proses perdamaian, baik di level nasional hingga lokal. Dengan tujuan mempelajari cara komunitas lokal, khususnya kelompok-kelompok pengajian perempuan, berperan sebagai agensi dalam upaya bina damai di ranah kontra-radikalisasi, penelitian ini mempertanyakan persepsi dan strategi kelompok pengajian perempuan sebagai representasi kelompok perempuan dan kelompok agamis di Kabupaten Cilacap dalam upaya-upaya kontra-radikalisasi dan bina damai. Lebih lanjut, artikel ini memberikan gambaran mengenai aktivitas-aktivitas bina damai dan kontra radikalisasi oleh kelompok pengajian perempuan di Cilacap dan menjelaskan bagaimana persepsi mereka tentang radikalisasi memengaruhi pemahaman sebagai agensi dalam rangkaian aktivitas kontraradikalisasi dan berperan dalam upaya mereka membangun fondasi bagi perdamaian positif di komunitas dengan penguatan ketahanan sosial melalui aktivitas-aktivitas sosial keagamaan